Single‐Shot Fabrication of Semiconducting–Superconducting Nanowire Devices. (17th June 2021) - Borsoi, Francesco; Mazur, Grzegorz P.; van Loo, Nick; Nowak, Michał P.; Bourdet, Léo; Li, Kongyi; Korneychuk, Svetlana; Fursina, Alexandra; Wang, Ji‐Yin; Levajac, Vukan; Memisevic, Elvedin; Badawy, Ghada; et al.
Abstract: Semiconducting–superconducting hybrids are vital components for the realization of high‐performance nanoscale devices. In particular, semiconducting–superconducting nanowires attract widespread interest owing to the possible presence of non‐abelian Majorana zero modes, which are quasiparticles that hold promise for topological quantum computing. However, systematic search for Majoranas signatures is challenging because it requires reproducible hybrid devices and reliable fabrication methods. This work introduces a fabrication concept based on shadow walls that enables the in situ, selective, and consecutive depositions of superconductors and normal metals to form normal‐superconducting junctions. Crucially, this method allows to realize devices in a single shot, eliminating fabrication steps after the synthesis of the fragile semiconductor/superconductor interface. At the atomic level, all investigated devices reveal a sharp and defect‐free semiconducting–superconducting interface and, correspondingly, a hard induced superconducting gap resilient up to 2 T is measured electrically. While the cleanliness of the technique enables systematic studies of topological superconductivity in nanowires, it also allows for the synthesis of advanced nano‐devices based on a wide range of material combinations and geometries while maintaining an exceptionally high interface quality. Abstract : Semiconducting–superconducting hybrids are vital components for the realization of nanoscale devices such as topological qubits. Here, a fabrication concept is introduced, enabling the in situ, selective, and consecutive depositions of superconducting and metallic layers on semiconducting nanowires forming hybrid junctions in a single shot. By eliminating conventional nanofabrication steps, all devices reveal sharp interfaces and hard gap induced superconductivity.